Project Based Learning for Cultivating Student Discipline: A Planning and Organizational Approach - Sarrayu, Anggraeni Eka; Karwanto, Karwanto; Roesminingsih, Erny; Khamidi, Amrozi (Electronic Journal of Education, Social Economics and Technology, 2025)
Student discipline is a critical factor in effective learning environments, yet traditional punitive approaches have shown limited success in fostering intrinsic motivation and self-regulation. This paper investigates how the planning and organizational aspects of project-based learning (PBL) contribute to cultivating student discipline, using a qualitative research approach involving classroom observations, teacher interviews, and student focus groups. The results indicate that effective PBL requires careful alignment with learning objectives, structured environments with clear expectations, and relevant, engaging projects. Student involvement in planning and decision-making processes enhances engagement, ownership, and responsible behavior, while collaborative group work fosters negotiation, conflict resolution, and social-emotional development. Incorporating real-world connections and authentic assessments increases the relevance of learning, leading to higher motivation, self-discipline, and improved academic and soft skills outcomes. These findings suggest that strategic implementation of PBL can create supportive, participatory, and meaningful learning environments that promote student discipline and prepare learners for broader societal challenges, including those relevant to the evolving demands of the renewable energy sector.